Scale up manufacturing approach for production of human induced pluripotent stem cell-derived islets using Vertical Wheel® bioreactors - Nidheesh Dadheech; Mario Bermúdez de León; Zofia Czarnecka; Nerea Cuesta-Gomez; Ila Tewari Jasra; Rena Pawlick; Braulio Marfil-Garza; Sandhya Sapkota; Kevin Verhoeff; Haide Razavy; Perveen Anwar; Abhineet Singh; et al. (npj Regenerative Medicine)
Abstract Advanced protocols show potential for human stem cells (SC)-derived islets generation under planar (2D) alone or three-dimensional (3D) cultures, but show challenges in scalability, cell loss, and batch-to-batch consistency. This study explores Vertical Wheel (VW)® bioreactor suspension technology to differentiate islets from human induced pluripotent stem cells, achieving uniform, transcriptionally mature, and functional SC-islets. A 5x increase in scale from 0.1 L to 0.5 L reactors resulted in a 12-fold (15,005–183,002) increase in islet equivalent count (IEQ) without compromising islet structure. SC-islets show enriched β-cell composition (~63% CPPT+NKX6.1+ISL1+), glucose responsive insulin release (3.9–6.1-fold increase), and reversed diabetes in STZ-treated mice. Single cell RNA sequencing and flowcytometry analysis confirmed transcriptional maturity and functional identity, similar to adult islets. Lastly, harvested SC-islet grafts demonstrate improved islet functionality and mature transcriptomic signatures. Overall, scale-up in VW® bioreactor technology enhances IEQ yield with minimal variability and reduced cell loss, offering a pathway for clinical-grade SC-islet production.